Identification and analytical characterization of nine synthetic cathinone derivatives N‐ethylhexedrone, 4‐Cl‐pentedrone, 4‐Cl‐α‐EAPP, propylone, N‐ethylnorpentylone, 6‐MeO‐bk‐MDMA, α‐PiHP, 4‐Cl‐α‐PHP, and 4‐F‐α‐PHP. Issue 8 (28th December 2016) - Liu, Cuimei; Jia, Wei; Li, Tao; Hua, Zhendong; Qian, Zhenhua
Abstract : Clinical and forensic toxicology laboratories are continuously confronted by analytical challenges when dealing with the new psychoactive substances (NPS) phenomenon. In this study, the analytical characterization of nine synthetic cathinones is described: 2‐(ethylamino)‐1‐phenylhexan‐1‐one ( N ‐ethylhexedrone1 ), 1‐(4‐chlorophenyl)‐2‐(methylamino)pentan‐1‐one (4‐Cl‐pentedrone2 ), 1‐(4‐chlorophenyl)‐2‐(ethylamino)pentan‐1‐one (4‐Cl‐ α ‐EAPP3 ), 1‐(3, 4‐methylenedioxyphenyl)‐2‐propylaminopropan‐1‐one (propylone4 ), 1‐(3, 4‐methylenedioxyphenyl)‐2‐ethylaminopentan‐1‐one ( N ‐ethylnorpentylone5 ), 1‐(6‐methoxy‐3, 4‐methylenedioxyphenyl)‐2‐methylaminopropan‐1‐one (6‐MeO‐bk‐MDMA6 ), 4‐methyl‐1‐phenyl‐2‐(pyrrolidin‐1‐yl)pentan‐1‐one ( α ‐PiHP7 ), 1‐(4‐chlorophenyl)‐2‐(pyrrolidin‐1‐yl)hexan‐1‐one (4‐Cl‐ α ‐PHP8 ), and 1‐(4‐fluorophenyl)‐2‐(pyrrolidin‐1‐yl)hexan‐1‐one (4‐F‐ α ‐PHP9 ). The identification was based on ultra‐high‐performance liquid chromatography‐quadrupole time‐of‐flight–mass spectrometry (UHPLC–QTOF‐MS), gas chromatography‐mass spectrometry (GC‐MS), and nuclear magnetic resonance (NMR) spectroscopy. The mass‐spectral fragmentations of these compounds following collision‐induced dissociation (CID) and electron ionization (EI) were studied to assist forensic laboratories in identifying these compounds or other substances with similar structure in their case work. To our knowledge, no analytical data about the compounds1–4, 7, and8 have appeared until now, making this the first report on these compounds. The GC‐MS data of5, 6 and9 has been reported, but this study added the LC‐MS, Fourier Transform Infrared (FTIR) and NMR data for additional characterization. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Nine synthetic cathinone derivatives N ‐ethylhexedrone, 4‐Cl‐pentedrone, 4‐Cl‐ α ‐EAPP, propylone, N ‐ethylnorpentylone, 6‐MeO‐bk‐MDMA, α ‐PiHP, 4‐Cl‐ α ‐PHP, and 4‐F‐ α ‐PHP were identified using UHPLC‐QTOF‐MS, GC‐MS, and NMR. The mass‐spectral fragmentations of these compounds following collision‐induced dissociation (CID) and electron ionization (EI) were studied to assist forensic laboratories in identifying these compounds or other substances with similar structure in their case work.